ANALISIS CORPORATE GOVERNANCE TERHADAP KINERJA PASAR - Arie Setyo Dwi Purnomo; M Boy Singgih Gitayuda (Universitas Islam Balitar, 2020)
This study aims to examine corporate governance on market performance in banking companies. The sample in this study is banking in the Indonesia Stock Exchange for the period 2011-2019. The results showed that corporate governance has a positive effect on banking performance by using Tobin Q and return on equity (ROE). Furthermore, there is additional information from the results of this study. The number of directors and independent commissioners has a positive influence. Whereas the presence of foreign board directors has a positive impact because the expertise they have is different from that of local directors. The number of meeting activities also has a positive effect on performance because the market sees that the supervisory and controlling activities of the directors' performance are in line with the expectations of shareholders. However, the existence of female directors and doctoral-educated directors has a negative effect because the socio-cultural aspects of Indonesian society are still patriarchal and the level of education does not always have the competencies and abilities needed